Piring Anyaman Lidi Siwalan "Sentuhan Kreatifitas Anyaman Daun Siwalan Desa Pragaan Daya" - Achmad Nur Kholis; Moch. Zeinal Furqon; Ika Tri Nuraini; Sumriyah Sumriyah (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
This research aims to explore the potential of siwalan skewer woven plates as a typical local product of Pragaan Daya Village, Sumenep, and consider the need for Intellectual Property Rights (IPR) protection for these products. The background of this research is the great potential of local handicraft products that have not been fully utilized and legally protected, so that they are at risk of unauthorized reproduction. The formulation of the problems raised includes the potential cultural and economic value of this product, as well as challenges in the IPR registration process. The research uses a qualitative method with a case study approach, involving in-depth interviews and participatory observation to collect data from artisans and local community leaders. The results of the study show that siwalan skewer woven plates have unique raw materials and traditional woven techniques that are inherited from generation to generation. IPR protection is expected to increase product added value, strengthen local identity, and encourage the economic welfare of the Pragaan Daya community. Support from the government is needed to facilitate the IPR registration process and overcome the obstacles faced by the community in understanding the procedures and registration costs.